2006
DOI: 10.1074/jbc.m602360200
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of Functional Antigenic Peptide Transporter TAP Requires Assembly of Pre-existing TAP1 with Newly Synthesized TAP2

Abstract: The transporter associated with antigen processing (TAP) is essential for the delivery of antigenic peptides from the cytosol into the endoplasmic reticulum (ER), where they are loaded onto major histocompatibility complex class I molecules. TAP is a heterodimeric transmembrane protein that comprises the homologous subunits TAP1 and TAP2. As for many other oligomeric protein complexes, which are synthesized in the ER, the process of subunit assembly is essential for TAP to attain a native functional state. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 28 publications
2
21
1
Order By: Relevance
“…Single-cysteine TAP subunits, expressed alone, yielded a single band of 174 and 150 kDa for TAP1 and TAP2, respectively, indicating the formation of homodimeric complexes (34,35). These homodimers, which form when one subunit is in excess (35), are most likely misfolded and thus inactive in peptide binding and translocation (17,25). This finding is in line with the observation that single cysteines placed in each X-loop can be cross-linked in the homodimer but not in the heterodimer (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Single-cysteine TAP subunits, expressed alone, yielded a single band of 174 and 150 kDa for TAP1 and TAP2, respectively, indicating the formation of homodimeric complexes (34,35). These homodimers, which form when one subunit is in excess (35), are most likely misfolded and thus inactive in peptide binding and translocation (17,25). This finding is in line with the observation that single cysteines placed in each X-loop can be cross-linked in the homodimer but not in the heterodimer (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The data presented in this paper also suggest a somewhat unconventional model whereby TAP1 ubiquitination and degradation do not result in a similar change in TAP2 abundance. However, previous studies have demonstrated that newly synthesized TAP2 requires TAP1 for appropriate folding and stability (43). Moreover, TAP2 is targeted for proteasomal degradation when it is expressed in the absence of TAP1 in T2 lymphoblastoid cells or TAP1 abundance is reduced in vitro (43).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have demonstrated that newly synthesized TAP2 requires TAP1 for appropriate folding and stability (43). Moreover, TAP2 is targeted for proteasomal degradation when it is expressed in the absence of TAP1 in T2 lymphoblastoid cells or TAP1 abundance is reduced in vitro (43). Conversely, introduction of TAP1 into TAP1-deficient melanoma cells markedly enhances TAP2 protein levels (44).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the ABC transporter TAP, this is even more challenging because (i) TAP functions as a heterodimeric complex, (ii) preformed TAP1 serves as a scaffold for the folding of TAP2 (44), and (iii) solubilized TAP is highly unstable and prone to aggregate or to dissociate into its subunits (21). Earlier attempts of TAP expression in human cells (45), Saccharomyces cerevisiae (46), and insect cells (20) allowed the investigation of some important aspects of the antigen translocation machinery.…”
Section: Discussionmentioning
confidence: 99%